If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + 0.6 = -30 Reorder the terms: 0.6 + 25x = -30 Solving 0.6 + 25x = -30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6' to each side of the equation. 0.6 + -0.6 + 25x = -30 + -0.6 Combine like terms: 0.6 + -0.6 = 0.0 0.0 + 25x = -30 + -0.6 25x = -30 + -0.6 Combine like terms: -30 + -0.6 = -30.6 25x = -30.6 Divide each side by '25'. x = -1.224 Simplifying x = -1.224
| 2q^2-12q=0 | | 2b+-8=2 | | 36+7n=6(5n+6)+3n | | 2(8m+3)=54 | | 2y+2=4x-2 | | 4z-7=11-2z | | 3a+2b-8a-3b= | | 7y-9=4y-12 | | 5r+20-7r=-16 | | -12-2x=-2(x+5) | | s=550 | | 6x+8x+10x=180 | | 12=3(6t+1) | | -2.8=-0.56(m+8) | | 7(4y-5)+3(5y+4)= | | 3m-17=52 | | 3(6x+24)=18x+72 | | 2q(q-6)=0 | | 2=2v-2 | | 6(1-4y)-5y=-8(3+4y) | | 6x+9y=2 | | 2k-4=12 | | 4-3x=-3+4x | | 3.5x+1.25= | | -25k=-150 | | 82=-65-x | | -(7x+6)=-3(1+2x) | | 4m^2-12a=-8 | | 7b+3-4b=3-3(-b+4) | | 7x+9-3x=25 | | 71=23-4x | | -4x+4-2x=-s(3x-3) |